Diagnosis and management of Alzheimer's disease--an update - Srinivas, P. (Malaysian Medical Association, 1999)
Alzheimer's disease (AD) has become recognised as a major cause of morbidity and mortality in the ageing population worldwide. Over 20 million people worldwide are affected by AD, which ensures that the disease imposes a major economic burden. Alzheimer's disease is a progressive neurodegenerative disorder with characteristic clinical and neuropathological features. Neurofibrillary tangles, neuritic plaques and amyloid angiopathy occur in varying severity in brains of patient's with Alzheimer's disease. Biological markers of AD allowing an early definitive premorbid diagnoses are currently not available. Memory loss for recent events is invariable and often the earliest prominent symptom. Language disorders, difficulties with complex tasks, depression, psychotic symptoms and behavioral changes are other common manifestations of AD. Diagnosis involves the early detection of cognitive decline and ruling out other causes of dementia like vascular dementia, Lewy body dementia, fronto-temporal degeneration or reversible causes like hypothyroidism. Acetylcholinesterase inhibitors have shown to be effective in mild to moderate AD in improving the cognitive function of patients in clinical trials. Caregiver intervention programs have considerable potential to improve both the caregiver and patient quality of life.